IN VITRO PROTEIN DIGESTIBILITY OF MILLET MEAL PREPARATIONS - V. DURGA RANI, JANE BRIDGET KANDEH, K. UMA DEVI , K. UMA MAHESWARI, T. SARAH KAMALA and (The Journal of Research, PJTSAU, 2019)
Six different millet products have been developed and standardized to serve as most common lunch dishes namely millet rice, kichidi and roti using traditional local recipe adopted for cereals. The overall mean in vitro protein digestibility (IVPD) of millet kichidi from 6 millets was 66.93 Â± 3.78%, and it was significantly high (P